1994
DOI: 10.1007/bf00212792
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods for monitoring the potential exposure of small children to pesticides in the residential environment

Abstract: A nine-home pilot study was conducted to evaluate monitoring methods in the field that may be used to assess the potential exposures of children aged 6 months to 5 years to pesticides found in the home environment. Several methods, some of which were newly developed in this study, were tested for measuring pesticide residues in indoor air, carpet dust, outdoor soil, and on the children's hands. Information was also collected on household characteristics, pesticides used and stored at the residence, and childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
189
3
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(198 citation statements)
references
References 9 publications
4
189
3
2
Order By: Relevance
“…2,69,75 According to the literature, children in general ingest about 50 mg/day house dust during the summer and 100 mg/day during the winter, when they spend more time indoors. 57,58 In the case of pica behavior (eating of non-nutritive substances), uptake can reach up to 2--30 g/day.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2,69,75 According to the literature, children in general ingest about 50 mg/day house dust during the summer and 100 mg/day during the winter, when they spend more time indoors. 57,58 In the case of pica behavior (eating of non-nutritive substances), uptake can reach up to 2--30 g/day.…”
Section: Resultsmentioning
confidence: 99%
“…57,58 In the case of pica behavior (eating of non-nutritive substances), uptake can reach up to 2--30 g/day. 2 Adults usually incorporate only 0.6 mg house dust per day, mainly because of dust settled on food and all kinds of surfaces combined with occasional hand to mouth contacts. 57,68 For adults, the mucous clearance of inhaled dust contributes significantly to the oral exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing attention is being paid to children's exposure to pesticide residues in housedust (Fenske et al, 1990;Lewis et al, 1994) due to reported associations between residential pesticide use and childhood leukemia (Lowengart et al, 1987;Shu et al, 1988;Buckley et al, 1989). Daniels et al (1997) reviewed 31 epidemiological studies published between 1970 and 1996 and reported that no-pest strips and frequent use of pesticides in the home may be strongly associated with childhood leukemia.…”
Section: Introductionmentioning
confidence: 99%